2002
DOI: 10.1038/sj.onc.1205641
|View full text |Cite
|
Sign up to set email alerts
|

Human cells bearing homozygous mutations in the DNA mismatch repair genes hMLH1 or hMSH2 are fully proficient in transcription-coupled nucleotide excision repair

Abstract: The transcription-coupled nucleotide excision repair (TCNER) pathway maintains genomic stability by rapidly eliminating helix-distorting DNA adducts, such as UV-induced cyclobutane pyrimidine dimers (CPDs), specifically from the transcribed strands of active genes. DNA mismatch repair (MMR) constitutes yet another critical antimutagenic pathway that removes mispaired bases generated during semiconservative replication. It was previously reported that the human colon adenocarcinoma strains HCT116 and LoVo (bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…3). This is consistent with the results of Rochette et al (9), showing a similar removal of CPDs from the transcribed strand of the c-jun and/or p53 gene in the MMR-deficient compared with the MMR-proficient cell lines after a UVC exposure of 15 J/m 2 to these same cell lines.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…3). This is consistent with the results of Rochette et al (9), showing a similar removal of CPDs from the transcribed strand of the c-jun and/or p53 gene in the MMR-deficient compared with the MMR-proficient cell lines after a UVC exposure of 15 J/m 2 to these same cell lines.…”
supporting
confidence: 82%
“…Using a strandspecific Southern blot-based assay, Mellon et al (8) reported that the MMR-deficient HCT116 and LoVo human adenocarcinoma cells (carrying mutations in the hMLH1 and hMSH2 genes, respectively) were defective in TCR of CPDs at the active dihydrofolate reductase gene locus. In contrast, using a ligation-mediated PCR that measures CPD removal at nucleotide resolution, Rochette et al (9) have reported recently that these same MMR-deficient adenocarcinoma cells are fully proficient in TCR. In addition, Sonneveld et al (10) reported that hMSH2-deficient murine embryonic fibroblasts are able to remove CPDs much more rapidly from the transcribed compared with the nontranscribed strand of active genes suggesting proficient TCR in murine embryonic fibroblasts, and Adimoolam et al (11) reported that hMLH1-deficient HCT116 cells are fully competent in TCR at the DHFR locus.…”
Section: Introductionmentioning
confidence: 99%
“…We reasoned that this methodological difference is unlikely to account for the observed contrariety in experimental outcome, because each of the aforementioned assays has been rigorously validated as a means to evaluate NER rates along the TS and NTS of active genes in living cells. For example, by using LMPCR, we previously reproduced the expected result, initially obtained via the Southern blot-based method (8), that CS-B cells are deficient in TCNER but not GNER of UV-induced CPD (31). Finally, we note that each of the above-mentioned assays quantifies precisely the same event, i.e., the lesion recognition͞incision step of NER as manifested by the disappearance of T4 endonuclease Vsensitive sites.…”
Section: Resultsmentioning
confidence: 60%
“…10 In a previous study, we compared repair of UVinduced CPD in the SW480 cell line and the LoVo cell line, derived from a colorectal adenocarcinoma. 11 The SW480 cell line was derived from a Duke's colon adenocarcinoma that was removed from a 50-year-old male patient. 12 The cell line was submitted to the American Type Culture Collection (ATCC) at passage 91 by Leibovitz in November 1978.…”
Section: Introductionmentioning
confidence: 99%